US SCHOLAR EXPLORES CURRENT TRENDS AND IMPACTS OF GLOBALISED EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 5 August 2016 – “There is the need for Universiti Sains Malaysia (USM) to be responsible in producing the workforce of the future, as well as for them to be thinking citizens. USM needs to offer access to balanced education to society, in areas of the sciences as well as the nonsciences,” said the USM Deputy ViceChancellor (Research and Innovation), Professor Dato’ Dr. Muhamad Jantan.